EVALUATION OF NON-ANTIBIOTICS ALONE AND IN COMBINATION WITH CEPHRADINE IN THE CURE RATES IN CLINICAL BUBALINE MASTITIS - M. Yousaf; G. Muhammad; M. Q. Bilal; S. Firyal (Journal of Animal and Plant Sciences, 2012)
Effect of 4 antibiotics viz; chlorpromazine Hcl, (CPZ), lidocaine Hcl (LID), Povidone-iodine (PI), and Dimethylsulphoxide (DMSO) either alone or their respective combinations with cephradine was evaluated. For this purpose 270 clinically mastitic quarters of 249 Nili-Ravi buffaloes were infused with either non-antibiotics alone (CPZ = 25mg + 39ml normal saline; Lid = 10ml (2%) + 30ml normal saline; PI = 10ml (10%) + 30ml normal saline; DMSO = 20ml + 20ml normal saline) or in combination with cephradine (Ceph) (500mg) for 5 days. The response to these 8 treatments was monitored in terms of Surf Field Mastitis Test (SFMT) and California Mastitis Test (CMT) based cure rates. Surf Field Mastitis Test (SFMT) based cure rate on day 14 post initiation of treatment was the highest (60%) in quarters treated with CPZ followed by those treated with PI (46.6%), Lid (43.3%), and DMSO (10%). Barring PI, all non-antibiotic antibacterials tested in vivo exhibited a synergy with cephradine (Ceph). Thus on day 14 post initiation of treatment, SFMT based cure rates in quarters treated with CPZ + Ceph, Lid + Ceph, PI + Ceph, and DMSO + Ceph were 66.6, 66.6, 50 and 66.6 percent, respectively. Surf Field Mastitis Test based quarter cure rates on day 28 post initiation of treatment with non-antibiotic antibacterials alone as well as their combinations with Ceph were similar to those recorded on day 14. California Mastitis Test (CMT) based percent quarter cure rates on day 14 and day 28 in non-antibiotic antibacterials treatment groups and in groups treated with non-antibiotic antibacterials + Ceph were almost similar to those recorded with SFMT on the corresponding time points.
Keywords: Non antibiotics; cure rates; surf field mastitis test; California mastitis test; buffalo; clinical mastitis